2016
DOI: 10.2134/jeq2015.03.0146
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of Antimicrobial Resistance Determinants in Composted and Stockpiled Beef Cattle Manure

Abstract: Windrow composting or stockpiling reduces the viability of pathogens and antimicrobial residues in manure. However, the impact of these manure management practices on the persistence of genes coding for antimicrobial resistance is less well known. In this study, manure from cattle administered 44 mg of chlortetracycline kg feed (dry wt. basis) (CTC), 44 mg of CTC and 44 mg of sulfamethazine kg feed (CTCSMZ), 11 mg of tylosin kg feed (TYL), and no antimicrobials (control) were composted or stockpiled over 102 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The Halocella genus, which was most relatively abundant in the middle sampling depth of the DDG compost, has only one species, Halocella cellulosilytica , a moderately halophilic, anaerobic cellulolytic bacterium [ 40 ]. The DDG compost did have significantly higher concentrations of ammonium (NH 4 + ), Mg 2+ , and total phosphorus, compared to the CON and CON C&D and inclusion of distillers’ grains in cattle diets typically increases the overall fibre content [ 11 ]. Thus, the increase in Halocella observed in the DDG compost may have resulted from differences in chemical composition compared to CON substrates, particularly the higher fibre content of the DDG treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Halocella genus, which was most relatively abundant in the middle sampling depth of the DDG compost, has only one species, Halocella cellulosilytica , a moderately halophilic, anaerobic cellulolytic bacterium [ 40 ]. The DDG compost did have significantly higher concentrations of ammonium (NH 4 + ), Mg 2+ , and total phosphorus, compared to the CON and CON C&D and inclusion of distillers’ grains in cattle diets typically increases the overall fibre content [ 11 ]. Thus, the increase in Halocella observed in the DDG compost may have resulted from differences in chemical composition compared to CON substrates, particularly the higher fibre content of the DDG treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, resistant bacteria and resistance determinants found in livestock feces can potentially increase in concentration if left untreated after excretion [ 8 , 37 ]. Composting of manure prior to application has been shown to be an effective method to reduce antimicrobial resistance determinants in cattle manure, compared to stockpiling [ 11 ]. Therefore it is important to study whether changes in the initial composition of compost affects the ability to reduce antimicrobial resistance.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Xu et al (2016) of beef cattle manure in Alberta, Canada, observed that erm (B) and tet (M) abundances were significantly lower in stockpiles 26 d after formation compared with initial abundances (Xu et al, 2016). Conversely, in the present study erm (B) and tet (M) abundances between samples on 0 and 28 d after stockpile formation were not significantly different (Supplemental Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Animal manure harbors ARB and ARG regardless of antimicrobial use since manure is densely populated with bacteria (Sharma et al, 2009; Udikovic‐Kolic et al, 2014; Vikram et al, 2017; Xu et al, 2016). Several studies have raised concerns that amending croplands with animal manure, including from animals produced without antimicrobial use, enduringly increases AMR levels in soil, resulting in increased human exposure to AMR via consumption of the produced crops (Ghosh and LaPara, 2007; McKinney et al, 2018; Udikovic‐Kolic et al, 2014).…”
mentioning
confidence: 99%
“…Xu et al (2016) compared two management practices for beef cattle manure, stockpiling and window composting, in terms of their effectiveness on reducing antimicrobial resistance genes (ARGs). The levels of sul (1), tet (B), and erm (X) in the manure declined by 0.5, 1.6 and 2.8 log units per gram of dry matter, respectively, after 102 days.…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%